Percutaneous coronary intervention of an obstructive left anterior descending artery with anomalous origin of right coronary artery - Dubey, Laxman (Isfahan Cardiovascular Research Center, Isfahan University of Medical Sciences, 2013)
Coronary artery anomalies are a rare type of congenital anomalies with an incidence of 1.3% during routine cardiac catheterization. Anomalous origin of the coronary arteries is considered an incidental finding without clinical significance. This case describes a patient in whom evaluation of chest pain revealed an obstructive left anterior descending artery as well as an anomalous right coronary artery arising from the left coronary sinus. The patient underwent successful percutaneous coronary intervention of the left anterior descending artery and was discharged home free of angina 3 days later.